Sistem Informasi Akuntansi Kas Kecil Pada Yayasan Kria Yudha Nusantara - Zahra, A’liyah; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2023)
The need for information quickly encourages companies or organizations to create new services in order to obtain information accurately and efficiently. The problem found in the research object of the Kria Yudha Nusantara Foundation is that it has not been able to produce the presentation of accounting reports related to petty cash disbursements quickly, precisely and accurately because the report management process is carried out manually using Microsoft Ecxel 2010 which makes it difficult to find, display and print report data every month. Therefore, a petty cash accounting information system is needed to facilitate the admin of the Kria Yudha Nusantara Foundation in managing petty cash reports. Using an object-oriented approach (Object Oriented Analysis and Design) using UML (Unified Modeling Language) to produce a prototype of a petty cash accounting information system design with a fluctuating method designed to manage adequate petty cash receipts and disbursements in order to monitor and control cash funds small.